2020
DOI: 10.1177/0890117120904015
|View full text |Cite
|
Sign up to set email alerts
|

Student Tobacco Use Behaviors on College Campuses by Strength of Tobacco Campus Policies

Abstract: Purpose: To examine the association between strength of policy and self-reported tobacco use behavior, controlling for demographic characteristics, polytobacco use, knowledge of campus tobacco policy, and perceived policy compliance by others. Design: Cross-sectional, online survey. Setting: Ten participating State University of New York (SUNY) campuses; 5 with designated smoking/tobacco use areas and 5 with 100% tobacco-free policies. Subjects: Convenience sample of students from SUNY campuses: only tobacco u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…These consistent differences in tobacco consumption suggest a critical role for policies to prevent tobacco use among the young adult population, especially the US-born. A study by Ickes et al [23], for example, found that students who attend campuses without a comprehensive smoke-free policy were more like to report tobacco use on campus compared to students on a tobacco-free campus (65% vs. 36%), respectively. Our findings support the need for comprehensive smoke-free policies targeted at young adults.…”
Section: Discussionmentioning
confidence: 99%
“…These consistent differences in tobacco consumption suggest a critical role for policies to prevent tobacco use among the young adult population, especially the US-born. A study by Ickes et al [23], for example, found that students who attend campuses without a comprehensive smoke-free policy were more like to report tobacco use on campus compared to students on a tobacco-free campus (65% vs. 36%), respectively. Our findings support the need for comprehensive smoke-free policies targeted at young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Policies are an effective way to prevent tobacco use among the young adult population. A study by Ickes et al [23], found that students who attend campuses without a comprehensive smoke-free policy were more like to report tobacco use on campus compared to students on a tobacco-free campus (65% vs 36%) respectively. There's the need for comprehensive smoke-free policies targeted at young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, o monóxido de carbonoo mesmo gás venenoso que sai do escapamento de automóveis; e o alcatrão constituído por aproximadamente 60 substâncias cancerígenas, como agrotóxicos e elementos radioativos. O fumo produzido pelos cigarros é um aerossol com mais de 4000 compostos químicos diferentes (Ickes et al, 2020).…”
Section: Epidemiologiaunclassified